Stages of Development of Scientific Perspectives on Tax Burden - Rakhimova Shakhlo Rajapboevna (Scientific Trends, 2025)
The article analyzes the historical formation and developmental stages of scientific perspectives on tax burden, examining its impact on economic development. The concept of tax burden, its evolution, interpretations across various economic schools of thought, and its influence on the economy are thoroughly explored. Additionally, the study investigates the advantages and disadvantages of tax burden for taxpayers, the directions of contemporary tax policy, and the levels of tax burden in different countries in relation to economic growth. The case of Uzbekistan is highlighted, focusing on the dynamics of tax burden in recent years and its effects on the business environment.
Keywords: Tax burden, economic development, tax policy, economic schools, investment, entrepreneurship, Keynesianism, Laffer curve, globalization.